The Relationship Between Dog-Related Factors and Owners' Attitudes Toward Pets: An Exploratory Cross-Sectional Study in Korea - Kim, Woo-Hyun; Min, Kyung-Duk; Cho, Sung-il; Cho, Seongbeom (Frontiers in Veterinary Science, 2020)
In Korea, there is a need for research on human–animal relationships because of an increase in the number of companion animals and positive changes in public perception toward them. Few studies have examined these changes. This epidemiological study investigates the characteristics of Korean dog owners and their pet dogs and identifies the owner- and dog-dependent factors that influence owners’ attitudes toward pets. We conducted a cross-sectional study of dog owners by asking them to complete a Pet Attitude Scale-based questionnaire about their dogs and themselves. The participants included 654 young adults between 19 and 39 years of age who lived in Seoul and owned dogs. We found that most dogs were owned by single, educated, high income men who preferred small purebred dogs. Most were also likely to underestimate their dog’s Body Condition Score (BCS). The multivariable logistic regression (odds ratio, OR) and the multiple linear regression (unstandardized coefficients, B) models suggested that positive pet attitudes were associated with nineseven factors: overweight (OR = 2.68, B = 5.28) orand a normal BCS (OR = 2.09, B = 5.58), having medical history related disease (OR =2.36, B = 6.38) and vaccination (OR = 2.10, B = 6.22), buying the pet dog (OR = 0.60, B=-3.85), having a small dog (≤ 10 kg) (OR = 1.66), visiting the veterinarian frequently (OR = 1.08, B = .39), spending more time with dog (OR = 1.23, B=1.32), and keeping other species in the house (B = -4.27). This study is the first to identify relationships between owner- and dog-dependent factors and pet owner attitude toward pets, all within a Korean cultural context. This study highlights factors associated with the development of relationships between pet dogs and their owners. The exploratory study is novel because it examines pet ownership in the context of Korean culture; previous pet ownership studies were set in the West and are analyzed with Western cultural values in mind.